Changes to inpatient versus outpatient hospitalization: Medicare's 2‐midnight rule. Issue 3 (31st December 2014) - Locke, Charles; Sheehy, Ann M.; Deutschendorf, Amy; Mackowiak, Stephanie; Flansbaum, Bradley E.; Petty, Brent
<x xml:space="preserve">Abstract</x> Outpatient versus inpatient status determinations for hospitalized patients impact how hospitals bill Medicare for hospital services. Medicare policies related to status determinations and the Recovery Audit Contractor (RAC) program charged with postpayment review of such determinations are of increasing concern to hospitals and physicians. We present an overview and discussion of these policies, including the recent 2‐midnight rule, the effect on status determinations by the RAC program, and other recent and pertinent legislative and regulatory activity. Finally, we discuss the future direction of Medicare status determination policies and the RAC program, so that physicians and other healthcare providers caring for hospitalized Medicare beneficiaries may better understand these important and dynamic topics. Journal of Hospital Medicine 2015;10:194–201. © 2014 Society of Hospital Medicine